2018
DOI: 10.1136/annrheumdis-2018-213023
|View full text |Cite
|
Sign up to set email alerts
|

Risk of preterm delivery and small-for-gestational-age births in women with autoimmune disease using biologics before or during pregnancy: a population-based cohort study

Abstract: These population-based data suggest that the use of biologics before and during pregnancy is not associated with an increased risk of preterm delivery or SGA births.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 25 publications
1
21
0
3
Order By: Relevance
“…Several studies have not found increased risks of adverse birth outcomes . Luu et al recently reported an increased risk for complications as a composite criterion, not specifying risk estimates for particular birth outcomes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have not found increased risks of adverse birth outcomes . Luu et al recently reported an increased risk for complications as a composite criterion, not specifying risk estimates for particular birth outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have not found increased risks of adverse birth outcomes. 31,32 Luu et al recently reported an increased risk for complications as a composite criterion, not specifying risk estimates for particular birth outcomes. 11 In other studies, risk estimates were slightly increased, or the prevalence of adverse birth outcomes differed between exposed and unexposed patients, but formal analyses were limited by few events.…”
Section: Strengths and Limitations In Relation To Other Studiesmentioning
confidence: 99%
“…Prolong inflammation can lead to placenta insufficiency and resulted in intrauterine growth restriction, miscarriage, preterm birth, pre-eclampsia and small for gestational age (SGA) [8,10,11]. Additionally, the use of disease-modifying anti-rheumatic drugs and biologics for disease control also raised the concern for pregnancy interruption [9,12]. Clear understanding of the potential adverse events not only provide patients with better preconceptional and prenatal counselling, but likely ease JIA mothers from inexplicable worries.…”
Section: Introductionmentioning
confidence: 99%
“…There are more than 70 diseases classified as autoimmune diseases at present, and their prevalence in the general population is about 7% (Cooper et al, 2009). Many autoimmune diseases have a significantly higher incidence in women than men, including SLE and RA, which may be caused by female sex hormones regulating the immune system through sex hormone receptors (Adams Waldorf and Nelson, 2008;Cai et al, 2019;Tsao et al, 2019). During pregnancy, the mother undergoes a series of physiological changes to ensure the healthy growth of the fetus, including immune, hormonal, and metabolic changes (Kumar and Magon, 2012).…”
Section: Autoimmune Diseasesmentioning
confidence: 99%